Legal Responsibility of Business Actors for Overclaims in the Cosmetics Industry is Linked to the Principle of Moral Integrity - Nurfauzi, Febri; Sari, Melia Putri Purnama; Afriana, Anita (JURNAL AKTA, 2025)
The cosmetic industry for skin care is increasingly growing in Indonesia, which is in line with the increasing business activities today. For women, cosmetics are one of the necessities. Along with such circumstances, overclaim actions in the cosmetics industry are rampant in Indonesia, this is related to business ethics that have not been fully implemented by business actors in Indonesia and the role of Law Number 8 of 1999 concerning Consumer Protection should be able to guarantee legal protection for consumers in Indonesia. The research method used in writing this article is normative juridical with qualitative juridical data analysis through collection from literature studies and linking the data obtained with laws and regulations, theories and legal principles.